Local instruction theory in the realistic mathematics education approach to improve students' mathematical proficiency in linear equation topics - Ode Samura, Asri; Im, Rosdiana; Ruslan, Jainudin (Beta: Jurnal Tadris Matematika, 2024)
[English]: The present study examines the improvement of students' mathematical proficiency in linear equation topics using local instruction theory (LIT) with a realistic mathematics education (RME) approach. This research employed a quasi-experiment, one-group pretest-posttest design. The sample was 37 secondary school students at SMP Negeri 1 South Halmahera, class VIII. The instrument used is a mathematical proficiency test consisting of 4 essay questions. Data were analyzed using the prerequisite test, Mann-Whitney test, Cohens (d) effect sizes test, and the gain value was determined. As a result, there are differences in students’ mathematical proficiency before and after implementing LIT through the RME approach. The influence of LIT with the RME approach on mathematics proficiency is very high. The students can define a linear equation, determine the slope of the line, construct a linear equation, integrate the linear graphs, and determine solutions for the linear equation problems. [Bahasa]: Penelitian ini mengkaji peningkatan kemampuan matematis siswa pada materi persamaan garis lurus menggunakan local instruction theory (LIT) melalui pendekatan realistic mathematics education (RME). Penelitian ini menggunakan desain quasi-eksperimen, one-group pretest-posttest. Sampel penelitian adalah siswa SMP Negeri 1 Halmahera Selatan kelas VIII sebanyak 37 orang. Instrumen yang digunakan berupa tes kemampuan matematis yang terdiri atas 4 soal essai. Data dianalisis menggunakan uji prasyarat, uji Mann-Whitney, uji Cohens (d) effect sizes, dan juga dilakukan perhitungan nilai gain. Hasil penelitian menunjukkan bahwa terdapat perbedaan kemampuan matematis antara sebelum dan setelah penerapan LIT dengan pendekatan RME. Pengaruh LIT dengan pendekatan RME terhadap kemampuan matematis siswa berkategori sangat tinggi. Siswa mampu mendefinisikan persamaan garis lurus, mampu menentukan kemiringan suatu garis lurus, dapat menyusun persamaan garis lurus, mengintegrasikan suatu grafik garis lurus, dan menentukan solusi dari masalah yang berkaitan dengan persamaan garis lurus.